Literature Review: Interpersonal Communication in Post-Broken Home Children - Ochameydiana, Ochameydiana; Hrp, Elina Herawaty; Sembiring, M. Alfin Eraninka; Lbs, M. Akbar Affandi; Andini, Andini; Tabina, Elsa; Harahap, Nursapia (Universitas Ibn Khaldun, 2024)
Background: Digital media has the greatest influence on interpersonal communication that occurs between children and adults, including communication that occurs in cases of broken homes. This is because the way media is used to interact with people has changed, resulting in the emergence of interpersonal conflict within the individual. This study aims to find out the role of digital media in interpersonal communication for children after a broken home. Research method: This study used a qualitative research method with inclusion criteria, namely journals published from 2017 to 2020. The samples used in this study were obtained from Google Scholar and Mendeley. Results: Interpersonal communication (Interpersonal) in children has a significant influence on children both from the child's learning process at school, then how to socialize at home, and the personality possessed by the child. Conclusion: Interpersonal communication (between individuals) is a direct and face-to-face human interaction that allows participants to observe verbal and nonverbal cues from others. (Mulyana, 2002) In the implementation of interpersonal communication, parents have the most important role for the child because if there is no establishing one Good communication between children and parents will hurt the child.